Informatics to Improve Medical Care of a Nation - Subramanian, M. (Methods of Information in Medicine, 1982)
At the Thirtieth World Health Assembly in 1977 the Member States of the World Health Organization endorsed the policy of developing their health care systems through the primary health care approach. The present paper is concerned with the application of certain significant features of informatics for the development and improvement of health care management in different countries.
Keywords: Primary Health Care; National Health Information Systems; Health Management Systems